A preparation method and application of antimony trioxide

Preparation of antimony trioxide by microemulsion method solves the agglomeration problems caused by the difficulty in particle size control and hydrolysis reaction in the prior art, and realizes the preparation of antimony trioxide at the nano-micron level, and shows good electricity in supercapacitors Chemical properties.

CN119160938BActive Publication Date: 2025-02-25HUNAN LOUDI HUAXING ANTIMONY IND
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411635028.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-02-25
Estimated Expiration
2044-11-15

AI Technical Summary

Technical Problem

The prior art has not been able to successfully prepare antimony trioxide at the cashier micron level, and in the hydrothermal method, antimony trioxide particles are prone to abnormally amplification and agglomeration due to hydrolysis reactions.

Method used

By using the microemulsion method, the organic antimony precursor and the polyol phase are added to the oil phase containing the first emulsifier and the oil, and the P/O emulsion is formed by high-speed stirring, and water containing the second emulsifier and water is added. In the phase, the reaction conditions are controlled to avoid the rapid occurrence of hydrolysis reactions, thereby controlling the size of antimony trioxide particles.

Benefits of technology

Antimony trioxide with a special porous micromorphic structure was successfully prepared, with particle size at the micro-nano level and exhibited good rate performance and capacity retention in supercapacitors.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119160938B_ABST
    Figure CN119160938B_ABST
Patent Text Reader

Abstract

The invention relates to the field of inorganic materials, and in particular to a preparation method and application of antimony trioxide. An organic antimony precursor and a polyol phase are added to an oil phase containing a first emulsifier and grease, and a P / O emulsion is obtained after high-speed stirring. The P / O emulsion is added to an aqueous phase containing a second emulsifier and water, and the mixture is stirred at a high speed for 1-30 seconds, and then stirred at a low speed for 30-90 minutes, and then allowed to stand, and a precipitate is collected by centrifugation, washed and dried. The method of the invention synthesizes antimony trioxide with a special porous microscopic morphology structure, so that the antimony trioxide becomes a very potential pseudocapacitor electrode material, and the specific capacity is about 500F / g at a current density of 2A / g, and after 2000 cycles at a current density of 2A / g, a relatively high capacity retention rate is still maintained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of inorganic materials, and in particular to a preparation method and application of antimony trioxide. Background Art

[0002] Antimony trioxide is a traditional chemical raw material, often used as a white pigment in paints, plastics, and synthetic rubber. It has unique physical and chemical properties and good flame retardant effects. It has a long history of use as a flame retardant. At the same time, antimony trioxide, as a transition metal oxide, has a high theoretical capacity, low price, abundant reserves, and relatively stable cycle performance. It can also be used as an electrode material for new energy batteries and pseudocapacitors.

[0003] At present, the preparation methods of antimony trioxide generally include alcoholysis, chemical reduction, microsol method, hydrothermal method, etc. Although the existing literature discloses the technical solution of using emulsifier TX-50 in the hydrothermal method for preparing antimony trioxide, there is no report on the preparation of nano-micron level antimony trioxide by microemulsion method. Summary of the invention

[0004] Purpose of the invention: In view of the above technical problems, the present invention proposes a preparation method and application of antimony trioxide.

[0005] The technical solutions adopted are as follows:

[0006] A method for preparing antimony trioxide:

[0007] The organic antimony precursor and the polyol phase are added to the oil phase containing the first emulsifier and oil, and stirred at high speed to obtain a P / O emulsion (oil-in-alcohol emulsion). The P / O emulsion is added to the water phase containing the second emulsifier and water, and stirred at high speed for 1-30 seconds, then stirred at low speed for 30-90 minutes, and then allowed to stand, and the precipitate is collected by centrifugation, washed and dried.

[0008] Furthermore, the organic antimony precursor is ethylene glycol antimony.

[0009] Furthermore, the polyol phase is a combination of dipropylene glycol and ethylene glycol in a mass ratio of 1-4:1-4.

[0010] Furthermore, the first emulsifier is any one or more combinations of Span-20, Span-40, Span-60 and Span-80.

[0011] Furthermore, the grease is white oil.

[0012] Furthermore, the second emulsifier is poloxamer.

[0013] Furthermore, the pH of the aqueous phase is 3-6.

[0014] Furthermore, the pH of the aqueous phase is adjusted by adding phosphate.

[0015] Furthermore, the rotation speed during the high-speed stirring is ≥5000r / min, and the rotation speed during the low-speed stirring is ≤50r / min.

[0016] The present invention also provides an application of antimony trioxide prepared by the above method in a supercapacitor.

[0017] Beneficial effects of the present invention:

[0018] The invention provides a method for preparing antimony trioxide. The invention utilizes the property that ethylene glycol antimony is soluble in ethylene glycol but insoluble in white oil, utilizes an oil phase to isolate ethylene glycol antimony from a weakly acidic water phase, avoids the rapid occurrence of a hydrolysis reaction leading to abnormal enlargement and agglomeration of generated antimony trioxide particles, and in the process of low-speed stirring reaction, due to the effect of shear force, a trace amount of water enters the polyol phase to undergo a hydrolysis reaction with the ethylene glycol antimony, thereby controlling the size of the generated antimony trioxide. Phosphate is added to the water phase to adjust the pH and enable the emulsified particles to be charged and repel each other, thereby improving the stability of the system. The method of the invention synthesizes antimony trioxide with a special porous microscopic morphology structure, making it a very potential pseudocapacitor electrode material, with a specific capacity of about 500 F / g at a current density of 2 A / g, and still having a high capacity retention rate after 2000 cycles at a current density of 2 A / g. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 This is the SEM image of antimony trioxide prepared in Example 1. DETAILED DESCRIPTION

[0020] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially. The techniques not mentioned in the present invention are all referenced to the prior art. Unless otherwise specified, the following examples and comparative examples are parallel experiments, using the same processing steps and parameters.

[0021] Embodiment 1:

[0022] A method for preparing antimony trioxide:

[0023] Mix 2 g of dipropylene glycol and 3 g of ethylene glycol to obtain a polyol phase;

[0024] Add 0.2 g of Span-80 to 20 g of white oil and mix well to obtain an oil phase;

[0025] 1 g of antimony glycol was added to the polyol phase, stirred to dissolve, and then added to the oil phase, and stirred at a high speed of 10000 r / min for 5 min to obtain a P / O emulsion;

[0026] 2 g of poloxamer 407 was added to 200 ml of deionized water and mixed, and then sodium dihydrogen phosphate was added to adjust the pH of the system to 5 to obtain an aqueous phase;

[0027] The P / O emulsion is added to the aqueous phase, stirred at a high speed of 10000 r / min for 30 seconds, then stirred at a low speed of 50 r / min for 60 minutes, and then allowed to stand for 24 hours. The precipitate is collected by centrifugation, and the product is repeatedly washed with deionized water and ethanol and dried to obtain antimony trioxide with a purity of ≥99.99%.

[0028] The surface morphology of the particles was tested using a ZEISS (EVO MA15) scanning electron microscope with a scanning voltage of 20 kV. The results showed that the particles were micro-nanoparticles with a porous structure. Figure 1 ;

[0029] The antimony trioxide and acetylene black prepared in this example are mixed in a mass ratio of 7:2 and fully ground to obtain a mixture 1; polyvinylidene fluoride (the mass is 0.5 times that of acetylene black) is added to an appropriate amount (about 0.5 mL) of N-methylpyrrolidone and fully ground to obtain a mixture 2; the mixture 1 is added to the mixture 2, and after fully grinding, the mixture is smeared on a pre-cut nickel foam disc, first dried in a 60° C. forced air drying oven for 12 h, and then immediately transferred to a vacuum drying oven and dried at 60° C. for 12 h as a working electrode of a three-electrode system for standby use;

[0030] The electrochemical performance test was carried out using an electrochemical workstation with a three-electrode system, in which platinum and mercury / mercury oxide were used as the counter electrode and reference electrode respectively, and 2 mol / L KOH solution was used as the electrolyte. Cyclic voltammetry and constant current charge and discharge tests were carried out, and the voltage window was 0-0.5 V. At a current density of 2 A / g, the specific capacity reached 526 F / g, indicating that its rate performance was good. After 2000 cycles at a current density of 2 A / g, the capacity retention rate was 95.4%.

[0031] Embodiment 2:

[0032] A method for preparing antimony trioxide:

[0033] Mix 1 g of dipropylene glycol and 4 g of ethylene glycol to obtain a polyol phase;

[0034] Add 0.2 g of Span-80 to 20 g of white oil and mix well to obtain an oil phase;

[0035] 1 g of antimony glycol was added to the polyol phase, stirred to dissolve, and then added to the oil phase, and stirred at a high speed of 10000 r / min for 5 min to obtain a P / O emulsion;

[0036] 2 g of poloxamer 407 was added to 200 ml of deionized water and mixed, and then sodium dihydrogen phosphate was added to adjust the pH of the system to 5 to obtain an aqueous phase;

[0037] The P / O emulsion is added to the aqueous phase, stirred at a high speed of 10000 r / min for 30 seconds, then stirred at a low speed of 50 r / min for 60 minutes, and then allowed to stand for 24 hours. The precipitate is collected by centrifugation, and the product is repeatedly washed with deionized water and ethanol and dried to obtain antimony trioxide with a purity of ≥99.99%.

[0038] The surface morphology was tested using a ZEISS (EVO MA15) scanning electron microscope with a scanning voltage of 20 kV. It was found through observation that the particles were micro-nanoparticles with a porous structure.

[0039] The electrochemical performance of antimony trioxide prepared in this example was tested by the method in Example 1. At a current density of 2 A / g, the specific capacity reached 505 F / g, indicating that its rate performance was good. After 2000 cycles at a current density of 2 A / g, the capacity retention rate was 94.1%.

[0040] Embodiment 3:

[0041] A method for preparing antimony trioxide:

[0042] Mix 2.5 g of dipropylene glycol and 2.5 g of ethylene glycol to obtain a polyol phase;

[0043] Add 0.2 g of Span-80 to 20 g of white oil and mix well to obtain an oil phase;

[0044] 1 g of antimony glycol was added to the polyol phase, stirred to dissolve, and then added to the oil phase, and stirred at a high speed of 10000 r / min for 5 min to obtain a P / O emulsion;

[0045] 2 g of poloxamer 407 was added to 200 ml of deionized water and mixed, and then sodium dihydrogen phosphate was added to adjust the pH of the system to 5 to obtain an aqueous phase;

[0046] The P / O emulsion is added to the aqueous phase, stirred at a high speed of 10000 r / min for 30 seconds, then stirred at a low speed of 50 r / min for 60 minutes, and then allowed to stand for 24 hours. The precipitate is collected by centrifugation, and the product is repeatedly washed with deionized water and ethanol and dried to obtain antimony trioxide with a purity of ≥99.99%.

[0047] The surface morphology was tested using a ZEISS (EVO MA15) scanning electron microscope with a scanning voltage of 20 kV. It was found through observation that the particles were micro-nanoparticles with a porous structure.

[0048] The electrochemical performance of antimony trioxide prepared in this example was tested by the method in Example 1. At a current density of 2 A / g, the specific capacity reached 521 F / g, indicating that its rate performance was good. After 2000 cycles at a current density of 2 A / g, the capacity retention rate was 94.9%.

[0049] Embodiment 4:

[0050] A method for preparing antimony trioxide:

[0051] Mix 3 g of dipropylene glycol and 2 g of ethylene glycol to obtain a polyol phase;

[0052] Add 0.2 g of Span-80 to 20 g of white oil and mix well to obtain an oil phase;

[0053] 1 g of antimony glycol was added to the polyol phase, stirred to dissolve, and then added to the oil phase, and stirred at a high speed of 10000 r / min for 5 min to obtain a P / O emulsion;

[0054] 2 g of poloxamer 407 was added to 200 ml of deionized water and mixed, and then sodium dihydrogen phosphate was added to adjust the pH of the system to 5 to obtain an aqueous phase;

[0055] The P / O emulsion is added to the aqueous phase, stirred at a high speed of 10000 r / min for 30 seconds, then stirred at a low speed of 50 r / min for 60 minutes, and then allowed to stand for 24 hours. The precipitate is collected by centrifugation, and the product is repeatedly washed with deionized water and ethanol and dried to obtain antimony trioxide with a purity of ≥99.99%.

[0056] The surface morphology was tested using a ZEISS (EVO MA15) scanning electron microscope with a scanning voltage of 20 kV. It was found through observation that the particles were micro-nanoparticles with a porous structure.

[0057] The electrochemical performance of antimony trioxide prepared in this example was tested by the method in Example 1. At a current density of 2 A / g, the specific capacity reached 518 F / g, indicating that its rate performance was good. After 2000 cycles at a current density of 2 A / g, the capacity retention rate was 94.3%.

[0058] Embodiment 5:

[0059] A method for preparing antimony trioxide:

[0060] Mix 4 g of dipropylene glycol and 1 g of ethylene glycol to obtain a polyol phase;

[0061] Add 0.2 g of Span-80 to 20 g of white oil and mix well to obtain an oil phase;

[0062] 1 g of antimony glycol was added to the polyol phase, stirred to dissolve, and then added to the oil phase, and stirred at a high speed of 10000 r / min for 5 min to obtain a P / O emulsion;

[0063] 2 g of poloxamer 407 was added to 200 ml of deionized water and mixed, and then sodium dihydrogen phosphate was added to adjust the pH of the system to 5 to obtain an aqueous phase;

[0064] The P / O emulsion is added to the aqueous phase, stirred at a high speed of 10000 r / min for 30 seconds, then stirred at a low speed of 50 r / min for 60 minutes, and then allowed to stand for 24 hours. The precipitate is collected by centrifugation, and the product is repeatedly washed with deionized water and ethanol and dried to obtain antimony trioxide with a purity of ≥99.99%.

[0065] The surface morphology was tested using a ZEISS (EVO MA15) scanning electron microscope with a scanning voltage of 20 kV. It was found through observation that the particles were micro-nanoparticles with a porous structure.

[0066] The electrochemical performance of the antimony trioxide prepared in this example was tested by the method in Example 1. At a current density of 2 A / g, the specific capacity reached 497 F / g, indicating that it has good rate performance. After 2000 cycles at a current density of 2 A / g, the capacity retention rate was 93.6%.

[0067] Comparative Example:

[0068] Commercially available antimony trioxide (purity ≥ 99.99%, particle size 1 μm, Hebei Ruihuang Metal Materials Co., Ltd.) was used as the sample;

[0069] The electrochemical performance of the antimony trioxide prepared in this example was tested by the method in Example 1. At a current density of 2 A / g, the specific capacity reached 419 F / g. After 2000 cycles at a current density of 2 A / g, the capacity retention rate was 77.6%.

[0070] Characterization of properties:

[0071] The antimony trioxide prepared in Examples 1-5 of the present invention was used as a sample, and a circulating dispersion sampling system was used to disperse the sample. A laser particle size distribution analyzer was used to test the particle size of the sample. The equivalent particle size (D10, D50, D90) was used to measure the change in the particle size of antimony trioxide, wherein D50 refers to the particle size value corresponding to the cumulative distribution percentage of 50%, also known as the median diameter. Particles with a particle size larger than the median diameter accounted for 50% of the entire sample, and particles smaller than the median diameter also accounted for 50%. The meanings of D10 and D90 are similar. The results are shown in Table 1 below:

[0072] ;

[0073] It can be seen from Table 1 above that the antimony trioxide prepared by the method of the present invention has a size of micro-nano level.

[0074] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing antimony trioxide, characterized in that: The organic antimony precursor and the polyol phase are added to the oil phase containing the first emulsifier and the oil, and the P / O emulsion is obtained after high-speed stirring. The P / O emulsion is added to the water phase containing the second emulsifier and water, and the mixture is stirred at high speed for 1-30 seconds, and then stirred at low speed for 30-90 minutes, and then allowed to stand, and the precipitate is collected by centrifugation, washed and dried. The organic antimony precursor is ethylene glycol antimony; The polyol phase is a combination of dipropylene glycol and ethylene glycol in a mass ratio of 1-4:1-4; The first emulsifier is any one or more combinations of Span-20, Span-40, Span-60 and Span-80; The grease is white oil; The second emulsifier is poloxamer; The pH of the aqueous phase is 3-6; The pH of the aqueous phase was adjusted by adding phosphate.

2. The method for preparing antimony trioxide according to claim 1, characterized in that: The rotation speed during the high-speed stirring is ≥5000r / min, and the rotation speed during the low-speed stirring is ≤50r / min.

3. Use of antimony trioxide prepared by the method for preparing antimony trioxide as claimed in claim 1 or 2 in supercapacitors.

Citation Information

Patent Citations

  • Multiple-effect type semi-synthetic micro-emulsion cutting solution

    CN102925271A

  • Polyol-in-oil nano-emulsion containing hydroxytyrosol as well as preparation method and application of polyol-in-oil nano-emulsion

    CN114099357A